The Application of Internet of Things (IoT) Technology in Agrotourism at Taman Inspirasi Strawberry Rasau Jaya Tiga - Hidayati, Rahmi; Ristian, Uray; Nirmala, Irma; Suhery, Cucu; Sari, Kartika (MEKONGGA: Jurnal Pengabdian Masyarakat, 2025)
Agrotourism is a form of tourism that utilizes agricultural land and supporting facilities to attract visitors. One of the emerging agrotourism destinations in Rasau Jaya Tiga is Taman Inspirasi Strawberry (Strawberry Inspiration Park), which serves as a local agriculture-based tourist attraction. With technological advancements in the agricultural sector, innovations such as the Internet of Things (IoT) a concept that connects physical devices to the internet to automatically collect and exchange data without human intervention have enabled the implementation of automated plant irrigation systems. In this Community Service Program, an IoT-based automatic irrigation system was designed and implemented for strawberry cultivation. The system employs soil moisture and temperature sensors to regulate watering automatically and can be monitored via mobile devices. In addition to system installation, outreach and training sessions were conducted for park managers and participants to ensure proper system operation. The implemented IoT system successfully reduced irrigation time by 53.3% and water consumption by 41.6% compared to manual methods. Participant satisfaction reached 92%, with the highest ratings in the usefulness of the technology and the effectiveness of the training. These findings demonstrate that the application of IoT technology is effective in supporting plant maintenance and enhancing both productivity and the overall appeal of the Taman Inspirasi Strawberry agrotourism site.